Ideal procurement system for Malaysian private sector construction clients / Wan Norizan Wan Ismail , Siti Sarah Mat Isa and Siti Nor Faizah Ab Malek - Wan Ismail, Wan Norizan; Mat Isa, Siti Sarah; Ab Malek, Siti Nor Faizah (2012)
Making the right choice of a procurement system at the onset ensures successful project delivery, a satisfied client, a successful service provider, and a reputable construction industry. Research has shown that client's requirements have not been properly addressed due largely to wrong choice of procurement systems. This research aims to identify the priority needs of clients and the appropriate procurement system that can ensure the delivery of satisfactory outcomes. Investigations were limited to the views expressed by private sector construction clients and consultants registered with their respective umbrella organizations in Malaysia. The descriptive survey method was used, which involved pilot interviews and structured questionnaire surveys. Results showed that client's would prefer a procurement system that can ensure the delivery of the project within time, budget and quality/specification targets. Other priority needs include fixed price tender, competitive or lowest price tenders, separate service provider for the design and management of the construction, life cycle cost, and risk preference and to accommodate variation orders without incurring financial penalties. Construction management type of procurement system with responsibilities monitoring and coordinating the construction process is the ideal procurement route that could best meet the needs of the Malaysian construction clients.